Development of transmitter and receiver circuit for automatic announcement in LRT train / Mohd Nazrul Fazli Mohd Foudzi - Mohd Foudzi, Mohd Nazrul Fazli
Remote control system using radio frequency increasingly popular compared to infrared. The advantage of radio is the ability of the signal to pass through objects and walls. Its range is also impressive about 100 meters and more (in free space) being typical. This paper presents a solution for LRT train announcement problem by using wireless radio frequency transmitter and receiver circuit to energize the automatic announcement circuit The circuit described generates ultrasonic sound of frequency between 315 Mhz to 350 Mhz. Transmitter which is placed at the station platform will generates ultrasonic sound and the receiver which is placed at the LRT train will senses ultrasonic sound from transmitter and switches "on" a relay. The relay is used to control the public address equipment. This project is one of the major part of the automatic announcement system which consists of complete block of automatic announcement system. The proposed project has two different circuit which is a transmitter that transmit the wireless radio frequency and a receiver to receive the signal transmitted. Then, the receiver output will connect to the automatic announcement circuit and activate it To develop this circuit there arc many software can be used such as p-spicc and Multisim ver7 to design and simulate the circuit and Protcl software to design the PCB board.